2006
DOI: 10.1111/j.1440-1746.2006.04089.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy alone for stage I (UICC T1N0M0) squamous cell carcinoma of the esophagus: Indications for surgery or combined chemoradiotherapy

Abstract: RT was a successful treatment for stage I esophageal cancer, and the treatment outcome using RT was nearly comparable to that of surgery. However, it is suggested that chemo-radiation should be considered in inoperable cases of submucosal cancer when the tumor is more than 5 cm in length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
(126 reference statements)
2
20
3
1
Order By: Relevance
“…A recent retrospective report by the Japanese Society of Therapeutic Radiology and Oncology Study Group did not validate the efficacy of IBT (16). Alternatively, our interim report demonstrated that both local control and survival rates for patients treated with external-beam radiotherapy (EBRT) combined with IBT were superior to those of patients treated with EBRT alone, but the difference did not reach a significance level (21). There were several shortcomings in the report, which would be addressed by (1) longer follow-up, (2) larger population size, and (3) adjustment of the difference in treatment periods between the group treated with EBRT alone and the group treated with EBRT plus IBT.…”
Section: Introductioncontrasting
confidence: 49%
“…A recent retrospective report by the Japanese Society of Therapeutic Radiology and Oncology Study Group did not validate the efficacy of IBT (16). Alternatively, our interim report demonstrated that both local control and survival rates for patients treated with external-beam radiotherapy (EBRT) combined with IBT were superior to those of patients treated with EBRT alone, but the difference did not reach a significance level (21). There were several shortcomings in the report, which would be addressed by (1) longer follow-up, (2) larger population size, and (3) adjustment of the difference in treatment periods between the group treated with EBRT alone and the group treated with EBRT plus IBT.…”
Section: Introductioncontrasting
confidence: 49%
“…Aucun de ces patients n'avait eu de traitement complémentaire (chimiothérapie, radiothérapie ou chirurgie) après l'EMR. Dans la littérature, les patients ayant des lésions pT1 traitées par radiochimiothérapie sans EMR au préalable ont une survie comprise entre 70 et 79 % [30][31][32][33]. Dans notre étude, les patients ont tous eu une EMR, et la survie est supérieure à 90 %.…”
Section: Discussionunclassified
“…Treatment selection for m3 or sm1 esophageal cancer include EMR/ESD, surgery and chemoradiotherapy. a search was conducted on PubMed for treatments using the keywords: superficial (or early) esophageal cancer, EMR, surgery and radiation for the period 1998-2008, and the results are shown in Table V ( [20][21][22]. No report discussed the long-term outcome of chemoradiation; thus Table V includes findings on only radiation.…”
Section: Discussionmentioning
confidence: 99%